Endogenous and uric acid-induced activation of NLRP3 inflammasome in pregnant women with preeclampsia - Matias, Mariana Leticia [UNESP]; Romao, Mariana [UNESP]; Weel, Ingrid Cristina [UNESP]; Ribeiro, Vanessa Rocha [UNESP]; Nunes, Priscila Rezeck [UNESP]; Borges, Vera Therezinha [UNESP]; Araujo, Joao Pessoa [UNESP]; Peracoli, Jose Carlos [UNESP]; Oliveira, Leandro de [UNESP]; Peracoli, Maria Terezinha [UNESP] (Public Library Science, 2015)
Preeclampsia (PE) is a specific syndrome of pregnancy, characterized by hypertension and proteinuria. This pathology is associated with hyperuricemia and elevated serum levels of inflammatory cytokines. Uric acid crystals may activate an intracellular complex called inflammasome, which is important for processing and release of inflammatory cytokines. This study investigated the state of monocyte activation, both endogenous and stimulated with monosodium urate (MSU), by gene expression of NLRP1 and NLRP3 receptors as well as their association with inflammatory cytokines expression. Monocytes were obtained from peripheral blood of 23 preeclamptic pregnant women, 23 normotensive pregnant women (NT) and 23 healthy non-pregnant women (NP). Inflammasome activation was evaluated by the gene expression of NLRP1, NLRP3, caspase-1, IL-1 beta, IL-18 and TNF-alpha by RT-qPCR in unstimulated monocytes (endogenous expression), or after cell stimulation with MSU (stimulated expression). The concentration of cytokines was assessed by ELISA. In preeclamptic pregnant women, gene expression of NLRP1, NLRP3, caspase-1, IL-1 beta and TNF-alpha by monocytes stimulated or not with MSU was significantly higher than in NT and NP groups. Stimulation of monocytes from preeclamptic and non-pregnant women with MSU induced increased gene expression of NLRP3, caspase-1 and TNF-alpha in relation to the endogenous expression in these groups, while this was not observed in the NT group. The cytokine determination showed that monocytes from women with PE produced higher endogenous levels of IL-1 beta, IL-18 and TNF-alpha compared to the other groups, while the stimulus with MSU led to higher production of these cytokines in preeclamptic group than in the NT group. In conclusion, the results showed increased basal gene expression of NLRP1 and NLRP3 receptors in monocytes from PE group. These cells stimulation with MSU demonstrates that uric acid plays a role in NLRP3 inflammasome activation, suggesting the participation of this inflammatory complex in the pathogenesis of preeclampsia.